2018
DOI: 10.1007/s12325-018-0816-8
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Multicentre Trial of Methoxyflurane for Acute Trauma-Related Pain in Helicopter Emergency Medical Systems and Hostile Environments: METEORA Protocol

Abstract: IntroductionThe inhalational analgesic low-dose methoxyflurane has been widely used by Australian ambulance services since 1975 and is now approved in Europe for emergency relief of moderate-to-severe trauma-related pain in conscious adult patients. The use of methoxyflurane in hostile environments is of special interest given its portability, ease of use and rapid onset of action. This trial will investigate the efficacy, tolerability and practicality of use of inhaled methoxyflurane in patients with moderate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“…Additional research on low-dose inhaled methoxyflurane could be useful to clearly establish its relative efficacy compared to opioids (including inhaled opioids) in patients with severe trauma pain, and in identifying the trauma patient profiles who could benefit the most from this acute pain treatment option. Finally, since METEORA 32 and METAMORPHOSIS studies are not yet complete, it is not possible to draw definitive conclusions on the use of methoxyflurane in hostile environments and on the organizational impact.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional research on low-dose inhaled methoxyflurane could be useful to clearly establish its relative efficacy compared to opioids (including inhaled opioids) in patients with severe trauma pain, and in identifying the trauma patient profiles who could benefit the most from this acute pain treatment option. Finally, since METEORA 32 and METAMORPHOSIS studies are not yet complete, it is not possible to draw definitive conclusions on the use of methoxyflurane in hostile environments and on the organizational impact.…”
Section: Discussionmentioning
confidence: 99%
“…The primary endpoint of the METEORA study is the proportion of trauma patients who achieve at least 30% reduction in pain score on the VAS scale within 10 minutes from methoxyflurane inhalation. 32…”
Section: Penasap Study -Methoxyflurane As Part Of Multi-modal Analgesiamentioning
confidence: 99%
“…Both studies showed high patient and healthcare professional (HCP) satisfaction with methoxyflurane treatment [18]. However, additional comparative studies versus the best currently available therapeutic options are needed to fully elucidate the place of methoxyflurane in emergency analgesia, including in extreme conditions such as helicopter rescue, which is the subject of an ongoing interventional study [27].…”
Section: Introductionmentioning
confidence: 99%
“…Low-dose methoxyflurane analgesia has also been approved in Canada, Eastern Europe, Latin America, South Africa and the Gulf area. 18,19 Recently completed 20,21 and ongoing studies 22,23 have investigated the effectiveness of methoxyflurane analgesia versus currently used analgesic treatments in the emergency setting. The InMEDIATE trial in Spanish EDs compared methoxyflurane with standard analgesic treatment (SAT, administered according to local practice) and reported a significantly greater decrease in pain intensity (on the Numerical Rating Scale [NRS 0-10 ] over 20 min; 2.47 vs 1.39), faster onset of pain relief (3 vs 10 min) and better patient and HCP ratings of pain control and comfort of treatment with methoxyflurane treatment.…”
Section: Introductionmentioning
confidence: 99%